2014
DOI: 10.4315/0362-028x.jfp-14-021
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Salmonella Contamination in Chicken Layer Farms in Three Caribbean Countries

Abstract: This study was conducted to investigate the demography, management, and production practices on layer chicken farms in Trinidad and Tobago, Grenada, and St. Lucia and the frequency of risk factors for Salmonella infection. The frequency of isolation of Salmonella from the layer farm environment, eggs, feeds, hatchery, and imported day-old chicks was determined using standard methods. Of the eight risk factors (farm size, age group of layers, source of day-old chicks, vaccination, sanitation practices, biosecur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 26 publications
10
34
4
2
Order By: Relevance
“…The isolation rate of Salmonella serovars in this study correlates with earlier study by Muhammad et al (2010) which reported isolation rate of 9.0 % from farms in Jos, Plateau state, Nigeria. It is however higher than 2.8 % reported in Caribbean countries (Adesiyun et al, 2014) Salmonella Typhimurium was the most frequent isolated serovar and this agree with previous work which also reported this serovar as one of the common serovars isolated from poultry in Nigeria (Orji et al, 2005). The isolation of invasive Salmonella such as serotype Typhimurium and other pathogenic salmonellae in this study highlights the risk of health hazards to consumers as contaminated poultry and poultry products may serve as source of infection to human food chain (Doaa, 2013).…”
Section: Discussioncontrasting
confidence: 55%
“…The isolation rate of Salmonella serovars in this study correlates with earlier study by Muhammad et al (2010) which reported isolation rate of 9.0 % from farms in Jos, Plateau state, Nigeria. It is however higher than 2.8 % reported in Caribbean countries (Adesiyun et al, 2014) Salmonella Typhimurium was the most frequent isolated serovar and this agree with previous work which also reported this serovar as one of the common serovars isolated from poultry in Nigeria (Orji et al, 2005). The isolation of invasive Salmonella such as serotype Typhimurium and other pathogenic salmonellae in this study highlights the risk of health hazards to consumers as contaminated poultry and poultry products may serve as source of infection to human food chain (Doaa, 2013).…”
Section: Discussioncontrasting
confidence: 55%
“…In the current study, size of farm was found to have a significant effect only on the frequency of resistance to kanamycin across the three countries and within Trinidad and Tobago; this may reflect differences in management systems and the use of antimicrobial agents, as reported elsewhere (4,32).…”
Section: Occurrence O F Resistance Among Salmonellamentioning
confidence: 46%
“…Standard methods were used to process the samples collected and to isolate Salmonella (4,6,23). Briefly, samples were preenriched in buffered peptone water (Oxoid, Ltd., Hampshire, England) for 18 to 24 h at 37°C and then were enriched in tetrathionate broth (Oxoid) and in Rappaport-Vassiliadis broth (Oxoid) incubated for 18 to 24 h at 37 and 42°C, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aux Caraïbes, 97,5% des fermiers utilisaient l'eau de robinet pour abreuver les animaux (Adesiyun et al, 2014).…”
Section: Pratiques D'élevage Avicoleunclassified